Four Lheidli T'enneh families' experiences and expectations of public education - Pighin, Jennifer Annaïs (Author); Greenwood, Margo (Thesis advisor); University of Northern British Columbia College of Arts, Social, and Health Sciences (Degree granting institution); Mills, Antonia (Committee member); Archibald, Jo-Ann (Committee member) (University of Northern British Columbia, 2016)
Initiatives designed to understand the discrepancy in graduation rates and investigate educational possibilities for First Peoples across Canada recognize it is vital to consider the local contexts of Indigenous peoples’ experiences with educational systems and their perspectives on learning. No recent studies have explored the local Lheidli T’enneh First Nations’ (LTFN) context relative to their member’s educational needs and expectations. This study engaged four multi-generational LTFN families’ lived experiences of public education including their expectations of the system. Their stories reflected three topic areas fundamental to this research: (1) relationships within the school, (2) pedagogy, and (3) curriculum. From a decolonizing Indigenous lens and using a qualitative methodology within an Indigenous research paradigm, common themes were identified from the participant narratives and are presented alongside existing literature. . Lheidli T’enneh First Nation Indigenous peoples’ education experience Education First Nations Education Indigenous Perspectives